PENGARUH KEPEMIMPINAN, KOMITMEN ORGANISASI, DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN, PENDIDIKAN, DAN PELATIHAN (BKPP) KOTA SEMARANG - Dwi Ditasari, 14.05.51.0111; Suharmanto, Toto (Students' Journal of Economic and Management, 2018)
The purpose of this study is to analyze the influence of Leadership, Organizational Commitment, and Motivation to Employee Performance at the Agency Staffing, Education, and Training (BKPP) of Semarang City. In this study the independent variables that affect the performance of employees are limited to Leadership, Organizational Commitment, and Motivation. The population in this study is the entire Employee Performance at the Agency Staffing, Education, and Training (BKPP) of Semarang City which amounted to 63 people. And selected as many as 63 respondents who serve as a sample. Data analysis techniques used are the validity test, reliability test and multiple linear regression analysis using IBM SPSS software version 20.0 to test and prove the research hypothesis. The result of multiple linear regression test shows that Leadership has positive and significant influence to employee performance, Organizational Commitment has positive and significant influence to employee performance, and Motivation has positive and significant influence to employee performance. Keywords: Leadership, Organizational Commitment, Motivation, and Employee Performance.